Relationship between personality traits and sexual function in symptomatic postmenopausal women. (December 2022) - Barbagallo, Federica; Cucinella, Laura; Tiranini, Lara; Martini, Ellis; Bosoni, David; Molinaro, Pietro; Battista, Federica; Albani, Francesca; Calogero, Aldo E.; Nappi, Rossella E.
Highlights: Personality traits may influence general health and many aspects of quality of life, including sexuality. Female sexual disorders are very common at midlife and many psychosocial variables are involved, along with biomedical factors. Harm avoidance, a serotonin-dependent personality trait, is significantly present in midlife women with sexual disorders. Harm avoidance significantly mediates the relationship between mood (anxiety and depression) and sexual function. Neuroendocrine balance may be relevant to the clinical expression of sexual disorders at menopause. Other behavioral and social factors may also play a role and deserve further attention. Abstract: Introduction: Female sexual function relies on a complex interplay of physical, psychosocial, and neurobiological factors. Over the last decades, increasing attention has been paid to the influence of personality traits on general health and many aspects of quality of life, including sexuality. Objective: To assess whether dimensions of the personality are related to the domains of sexual function (desire, arousal, lubrication, orgasm, satisfaction, and pain) in symptomatic postmenopausal women. Mood was also investigated to explore its association with female sexual dysfunction (FSD). Methods: Validated questionnaires to assess sexual function [the Female Sexual Functioning Index (FSFI)], mood [the State-Anxiety Inventory (STAI), and Zung Self Rating Depression Scale (SDS)], and personality traits [the Tridimensional Personality Questionnaire (TPQ)] were filled in by 130 early postmenopausal women experiencing hot flushes (≥30/week). Results: 61.5 % ( n  = 80) of the women had an FSFI total score lower than 26.55, the standard cut-off for FSD. A clinical state of anxiety was present in 53.8 % ( n  = 70), whereas only 12.3 % ( n  = 16) showed clinically relevant depressive symptoms. According to the FSFI cut-off score, women with sexual disorders had statistically significantly higher levels of anxiety, depression ( p  < 0.001 for both), and harm avoidance (HA) ( p  = 0.004) than women without such disorders. Significantly higher levels of anxiety were found in women in the lower quartile (LQ) of the distribution of the total FSFI score than in women in both the interquartile range (IQR) and in the upper quartile (UQ) ( p  < 0.05). Moreover, women in the UQ had a lower grade of depression and HA than others ( p  < 0.05). The Sobel test showed that the personality trait HA significantly mediated the relationship between anxiety and FSFI total score (Z = -2.19, p  < 0.05) and between depression and FSFI total score (Z = −2.35, p  < 0.05). Conclusions: The present data suggest the personality trait HA is relevant to sexual function and mediates the impact of mood on FSD in symptomatic menopausal women. In clinical practice, the use of validated psychometric tools for mood screening is useful to establish appropriate diagnosis and treatment of sexual disorders in menopausal women. Moreover, the assessment of personality traits could provide additional information that directs clinicians towards an increasingly tailored and multidimensional treatment of FSD.